2022
DOI: 10.6007/ijarems/v11-i2/13335
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Competitive Advantage (CA) Through the Role of Training and Compensations Practices on Innovative Work Behavior (IWB): A Study in Jordan Islamic Banks

Abstract: Effective training and compensation system are important for modern industries that aim to gain Competitive Advantage (CA) which is one of the key factors for companies' survival. A skilled workforce that reflec innovative work behavior (IWB) are an important element for companies to remain competition. This study aims to determine the relationship between training, direct compensation, and IWB, and then analyze the effect of IWB on CA with the moderating effect of indirect compensation. This study had been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The numbers used in the description come from previously published research, wh ich indicated a range of values for measuring the magnitude of the variables and objects in question. Researchers that have done descriptive statistics, including Siron and Tasripan (2012) and Qawasmeh, Darqal, and Qawasmeh (2013) provide values that are used to understand the assessment of the level of the mean. The mean value and its implications are shown in Table 3.…”
Section: Descriptive Information Of Variablesmentioning
confidence: 99%
“…The numbers used in the description come from previously published research, wh ich indicated a range of values for measuring the magnitude of the variables and objects in question. Researchers that have done descriptive statistics, including Siron and Tasripan (2012) and Qawasmeh, Darqal, and Qawasmeh (2013) provide values that are used to understand the assessment of the level of the mean. The mean value and its implications are shown in Table 3.…”
Section: Descriptive Information Of Variablesmentioning
confidence: 99%
“…Table 2 presents the outer model assessment results, which includes mean and standard deviation scores for all latent factors. Most items scored above 3.0, indicating a satisfactory performance (Qawasmeh et al, 2013). The outer model was also evaluated based on composite reliability (CR), factor loadings (FL), average variance extract (AVE), and discriminant validity (Hair Jr et al, 2021).…”
Section: Assessment Of the Reflective Measurement Modelmentioning
confidence: 99%